KESEPADANAN STRUKTUR KALIMAT PADA ARTIKEL KRIMINAL RADAR PEKALONGAN - Mochammad Chamdi Rochmat; Riska Yuliyanti (LPPM Universitas Pekalongan, 2017)
Equivalence structure is a balance between ideas or thoughts and structure of the language used, the proportionality of mind shown by the integrity and coherence of idea or ideas on that sentence, while the equivalence structure shown by the clarity of the presence of subject and predicate, not the subject of a double, the absence of conjunctions intrakalimat used in a single sentence, and the absence of the word